Rekonstruksi Epistemologi Hukum Islam: Analisis Pemikiran Fazlur Rahman sebagai Fondasi Kurikulum Pendidikan Syariah Modern - Dinata Firmamansyah; Sumarta; Rosidin; Kusyana (Penerbit Hellow Pustaka, 2025)
Contemporary Islamic legal education faces serious epistemological challenges due to the dominance of normative–doctrinal approaches that tend to be ahistorical and insufficiently responsive to modern social dynamics. This condition limits the capacity of Sharia education graduates to formulate Islamic legal solutions that are contextual and oriented toward public welfare (maslahah). This article aims to critically examine Fazlur Rahman’s thought on the epistemology of Islamic law and to formulate its implications for the reconstruction of modern Sharia education curricula. Employing a qualitative approach with a philosophical–critical orientation, this study is based on library research drawing upon Fazlur Rahman’s major works, classical uṣūl al-fiqh literature, Islamic legal philosophy, and relevant contemporary studies. The analytical methods applied include content analysis and hermeneutics, with Fazlur Rahman’s Double Movement theory serving as the main analytical framework. The findings indicate that Rahman’s epistemology particularly his distinction between normative Islam and historical Islam, as well as his contextual approach to revealed texts offers an alternative paradigm capable of overcoming the stagnation of Islamic legal hermeneutics. The Double Movement theory is shown to be epistemologically relevant as a foundation for designing Sharia education curricula that are methodologically oriented, integrative, and context-sensitive. This article contributes to the discourse on the epistemology of Islamic legal education by proposing a conceptual framework for reconstructing Sharia curricula that are adaptive to the challenges of modernity without compromising their normative authority.